Superior company performance, growth and agility in technology-based firms: a sector-based analysis. (19th September 2007) - O'Regan, Nicholas; Sims, Martin
There is a dearth of research on superior company performance and growth in technology-based firms. Furthermore, the majority of literature in this area focuses on large firms while research on smaller firms is underdeveloped. This paper investigates the impact of agility on the performance of technology manufacturing firms. No correlations were found between agility and performance when the sample was considered as a homogenous one. However, when a sectoral approach is taken, there are statistically significant correlations between agility and performance in Electronics, Electrical and IT?Software firms only.